Soft Power and Stress: The Health Impacts of Indonesian Soap Operas on Malaysian Millennials - Perdana, Rangga Cipta; Kadir, Ernida; Gempita, Genta Iverstika (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: The onslaught of Indonesian popular culture in Malaysia is an inevitable phenomenon. It enters without being prevented because of its presence in addition to the factor of technological sophistication, also because of the demand of many Malaysian audiences. The number of soap operas has infuriated certain circles. The reason is that the Indonesian culture that is born in Indonesian soap operas is shredded and superstition and it is not in accordance with the culture in Malaysia. All of this raises concerns that the presence of Indonesian culture will affect the identity, religion, and language, of the local community. Aims: This study aims to investigate and looking at the extent of the impression of Indonesian popular culture in Malaysia and to see the perception of Malaysian society, which is predominantly Muslim, in accepting non-Islamic elements aired in one of Indonesia's popular cultural products and see to what extent this affects emotional health, mental health and identity formation. Methods: To achieve the objectives and in order to avoid subjective views, this study is conducted in a controlled manner, namely by collecting data that supports presumptions, assumptions, and theories and also collecting opposing facts so that conclusions are not based on wishes, but what is found empirically. The data collection techniques in a qualitative approach can be done through observation, unstructured interviews, conversations, oral history and text analysis by using the basic question, namely Open-Ended questions. This is type of question allows respondents to answer more deeply and unexpectedly because the answers given will be subjective, according to the views of those people. Answers from open-ended questions can make us discover unknown and more in-depth topics about a study. Conclusion: Indonesian soap operas, as a form of soft power, have the capacity to influence the cultural and psychological landscape of Malaysian millennials. The consumption of such media can lead to stress, emotional fatigue, and identity conflicts, particularly when the content challenges established cultural and religious norms. By understanding the complex interplay between cultural influence and mental health, future research can focus on developing media literacy strategies and providing psychological support to help viewers navigate the potential stressors of cross-cultural media consumption.